2021
DOI: 10.7759/cureus.20213
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Arterial Stiffness and Resistance Training

Abstract: Exercise is a critical factor that impacts arterial stiffness. In this narrative review, we noted multiple findings that could not be reconciled with one another. Some studies indicated that arterial stiffness increases after a regimen of resistance training. However, such studies were limited by a lack of specification of the resistance training protocols, as well as varying results reported from different areas of the body, undermining the internal validity of the studies. Another factor explored in this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This can strengthen the argument that resistance and endurance training does not affect the vascular function, and moderate‐intensity endurance/resistance training causes no significant change in arterial stiffness of old male Wistar rats with HFD/STZ‐induced T2D. This indicates that the impact of endurance/resistance training on vascular function of old male Wistar rats with HFD/STZ‐induced T2D is not as great, or the resistance training performed was not effective at changing vascular function biomarkers, which could be the same with many of the studies showing no change in vascular function (Tabaie et al, 2021 ). Different studies showed no significant changes in vascular function following resistance training (Augustine et al, 2014 ; Croymans et al, 2014 ; Kujawski et al, 2018 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This can strengthen the argument that resistance and endurance training does not affect the vascular function, and moderate‐intensity endurance/resistance training causes no significant change in arterial stiffness of old male Wistar rats with HFD/STZ‐induced T2D. This indicates that the impact of endurance/resistance training on vascular function of old male Wistar rats with HFD/STZ‐induced T2D is not as great, or the resistance training performed was not effective at changing vascular function biomarkers, which could be the same with many of the studies showing no change in vascular function (Tabaie et al, 2021 ). Different studies showed no significant changes in vascular function following resistance training (Augustine et al, 2014 ; Croymans et al, 2014 ; Kujawski et al, 2018 ).…”
Section: Discussionsupporting
confidence: 66%
“…This indicates that the impact of endurance/resistance training on vascular function of old male Wistar rats with HFD/STZ-induced T2D is not as great, or the resistance training performed was not effective at changing vascular function biomarkers, which could be the same with many of the studies showing no change in vascular function (Tabaie et al, 2021). Different studies showed no significant changes in vascular function following resistance training (Augustine et al, 2014;Croymans et al, 2014;Kujawski et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…The unfavorable effects of resistance exercise on arterial stiffness rely on training intensity. Some studies have suggested that arterial stiffness is increased by high-intensity resistance exercise, but it is decreased by low-intensity resistance training [8]. Other studies have demonstrated that arterial stiffness decreases notably irrespective of resistance training intensity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that arterial stiffness is increased by high-intensity resistance exercise, but it is decreased by low-intensity resistance training [8]. Other studies have demonstrated that arterial stiffness decreases notably irrespective of resistance training intensity [8]. This inconsistent finding leads to the discrepancy in performing resistance training on arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness has been shown to acutely increase during RE, 8 which can last for approximately 1 h during the recovery following exercise, 9 and the magnitude of increase vary by the intensity of exercise. 10 However, very few studies on how RE with BFR alters this acute arterial stiffening response to RE showed conflicting findings, where acute LIRE with BFR demonstrated both positive and negative effects on arterial stiffness in healthy young people. 11 In addition, original data indicated possible safety concerns over BFR that restriction of blood flow to the working muscles may exaggerate cardiovascular stress during exercise.…”
Section: Introductionmentioning
confidence: 99%